Diagnostic concordance of metabolic syndrome according to different criteria in adult persons living at height - Medrano-Porras, Brian Kenny (2020)
Introduction. The metabolic syndrome is made up of a group of clinical entities that increase the risk of cardiovascular disease and diabetes mellitus. 2; which have increased in recent years. Objective. To compare the diagnostic concordance of the metabolic syndrome, according to the diagnostic criteria of the International Diabetes Federation (FID) and the National Cholesterol Education Program (PNEC-ATP III) in an adult population living at 3,270 m.a.s.l. Methods. An observational, cross-sectional and analytical study was designed. The sample was determined with inclusion and exclusion criteria, in a simple random way. Laboratory tests were performed on an empty stomach. The kappa coefficient (k) was used to determine the degree of agreement. Results. 43 (100 %) people were included. 58.1 % were over 60 years old. The frequency of the Metabolic Syndrome was 27.9 % (12), according to the criteria of the FID and 20.9 % (9), according to the criteria of the PNEC-ATP III. The frequency of metabolic syndrome increases with increasing age, especially after the age of 50 and is more common in overweight women. Between both diagnostic criteria an assessment of the kappa coefficient of 0.812 was found. Conclusion. There is a high concordance between the diagnostic criteria used by the FID and PNEC-ATP III guidelines to make the diagnosis of metabolic syndrome in residents living at height.